Storage life study on five brands of white pan bread - Muego, Kathleen Faith Fajardo; Rillo, Belen O. (1983.)
The storage life of five brands of white pan bread was studied. In the first phase, the changes occur on white an bread during storage at room temperature (28-31°C)and at 46066% relative humidity were determined. The moisture content of the crust increased with storage time while the moisture content of the crumb decreased. The bread lost its compressibility with storage. Significant differences exist among the samples taken from different storage days of Brand C and D. Microbiological examination led to the isolation of molds that may possibly be Rhizopus, Penicillium, Aspergillus, or Geotrichum. Brand B had the longest storage life, seven days, Brand C three days, and Brand D four days. In the second phase, the presence of acetic and/or propionic acids was established using paper chromatography. Brand A and E contained both acetic and propionic acids, Brand B and D had propionic acid only, and Brand C had acetic acid only. Identification of the packaging material done in Phase III revealed that all the brands had polyethylene as their wrapping material.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Bread -- Shelf-life dating